Nursing Diagnoses Of Patients With Neurological Disorders In Ward - Suyanto, Suyanto (Universitas Muhammadiyah Semarang, 2018)
Neurological disorders consist of stroke, meningitis, neurosurgery. Stroke is a condition where there is an attack on the blood vessels of the brain, either in the form of a blocked or ruptured blood vessel. The role of nurses as providers of nursing services is determined from the nursing diagnosis. The study wants to find out the main nursing diagnoses that appear in neurological disorders, especially stroke cases. Descriptive design was used in this study with a sample of 30 cases of patients who experienced neurological disorders using purposive sampling. There were 4 (four) main diagnoses that emerged, namely physical mobility disorders as many as 22 cases (73%), risk of ineffective cerebral perfusion and nutrition deficit of each of 19 cases (63.3%), decreased intracranial adaptive capacity by 9 cases (30 %). Nursing diagnosis in patients in the care ward is more dominant in the rehabilitation phase. Perhaps more research about nursing diagnosis of neurological disorder in emergency departement.